2019
DOI: 10.1093/jas/skz164
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of vascular endothelial growth factor A (VEGFA) gene expression in granulosa and theca cells of cattle1

Abstract: Vascular endothelial growth factor A (VEGFA) stimulates angiogenesis and is associated with increased vascularity in ovarian follicles of cattle. The objectives of this study were to investigate the developmental and hormonal regulation of VEGFA expression in ovarian granulosa and theca cells (TC) of cattle. Bovine ovaries were collected from a local slaughterhouse and granulosa cells (GC) and TC were collected from small (SM; 1 to 5 mm) and large (LG; 8 to 20 mm) follicles. Cells were collected fresh or cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 83 publications
(136 reference statements)
0
12
0
Order By: Relevance
“…The VEGFA gene, which encodes a vascular endothelial growth factor is upregulated in cancer tumors and its expression is correlated with tumor stage and progression [ 35 ]. In bovine, the VEGFA gene has also been associated with angiogenesis and increased vascularity in ovarian follicles [ 36 , 37 ], being considered an important regulator of placental development and function [ 38 ]. This gene plays an important function in the better supply of oxygen and nutrients to tissues, as well as in the tissue repair process after damage [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VEGFA gene, which encodes a vascular endothelial growth factor is upregulated in cancer tumors and its expression is correlated with tumor stage and progression [ 35 ]. In bovine, the VEGFA gene has also been associated with angiogenesis and increased vascularity in ovarian follicles [ 36 , 37 ], being considered an important regulator of placental development and function [ 38 ]. This gene plays an important function in the better supply of oxygen and nutrients to tissues, as well as in the tissue repair process after damage [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…bovine, the VEGFA gene has also been associated with angiogenesis and increased vascularity in ovarian follicles [36,37], being considered an important regulator of placental development and function [38]. This gene plays an important function in the better supply of oxygen and nutrients to tissues, as well as in the tissue repair process after damage [39].…”
Section: Plos Onementioning
confidence: 99%
“…The results of the KEGG analysis indicated that TGFβ1I1 is involved in the regulation of the VEGF signaling pathway. VEGFA, a gene encoding a heparin-binding protein, plays an important role in angiogenesis by inducing the proliferation and migration of vascular endothelial cells [ 52 ]. VEGF, as an angiogenic factor, binds to corresponding receptors on the follicular granulosa cell membrane to trigger downstream signaling cascades and promote follicle development [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The thecal vasculature is well developed in healthy follicles and breaks down in atretic follicles. The major proangiogenic factors, FGF2 and vascular endothelial growth factor (VEGF), are expressed in follicles and are under endocrine or paracrine control, as demonstrated by the ability of BMP4 to stimulate VEGFA mRNA levels in vitro in the bovine theca (Nichols et al 2019). In a bovine theca-endothelial cell coculture system, endothelial tubes form during culture, and angiogenesis is inhibited by TGFB1 or BMP6 and stimulated by a combination of VEGF and FGF2 (Mattar et al 2020).…”
Section: Resurrection Of the Thecamentioning
confidence: 99%